Kemampuan Asertif melalui Layanan Penguasaan Konten dengan Metode Diskusi Kelompok dan Bermain Peran - LL. Zihnan Munir (AS-SABIQUN, 2019)
This study aims to test and prove from the formulation of the problem. This type of research is experimental research. The study population was all students of class XI IPA. The research technique is a total sampling technique, because the total population is only 20 students. Data collection uses a psychological scale with an assertive ability scale instrument of 72 items. This instrument has been tested for use. The method of data analysis uses percentage descriptive and Wilcoxon test. The results showed that before getting treatment included in the low category with an average percentage of 52% and after getting treatment the average percentage was 72% included in the high category, resulting in an increase of 20%. Wilcoxon test results show the value obtained Z count = 3, 81> Z table = 1.96, the results are significant, that is, there is a significant difference between before and after getting content mastery service with group discussion and role playing methods, so Ha is accepted and Ho is rejected, thus indicating an increase in assertive ability of students between before and after the content mastery service is given by the method of group discussion and role playing, therefore the proposed hypothesis can be accepted. This means assertive ability can be improved by content mastery services with group discussion and role playing methods